Selective turn-on fluorescence detection of Vibrio parahaemolyticus in food based on charge-transfer between CdSe/ZnS quantum dots and gold nanoparticles. (October 2017) - Liu, Yushen; Zhao, Chao; Fu, Kaiyue; Song, Xiuling; Xu, Kun; Wang, Juan; Li, Juan
Abstract: Vibrio parahaemolyticus ( V. parahaemolyticus ) is one of the most common food-borne pathogens found along the east coast of China, Japan, and several southeast Asian countries, where marine foods are frequently consumed. Thus it is of great interest to establish a fast, sensitive and robust analytical assay for V. parahaemolyticus detection. Herein, we report a V. parahaemolyticus -specific egg yolk antibody (IgY), extracted from the egg yolks of immunized hens with inactivated V. parahaemolyticus bacteria. By immobilizing IgY onto the surface of gold nanoparticles (AuNPs) through electrostatic self-assembly, a detection system was developed based on charge-transfer quenching fluorescence, which contains core/shell CdSe/ZnS quantum dots (QDs), IgY-AuNPs and free AuNPs. In this strategy, the IgY-AuNPs were induced to aggregate quickly in the presence of target V. parahaemolyticus, resulting in a rapid fluorescence response of the QDs. More importantly, the convenient turn-on fluorescent detection system exhibited excellent selectivity over the other bacteria. Furthermore, this facile one-step method can detect V. parahaemolyticus at low concentrations of 10 cfu/mL without pre-enrichment and can be applicable for the detection of V. parahaemolyticus in real food samples. With the advantage of simplicity, rapidness, sensitivity, and specificity, this proposed approach shows promise as a successful application of V. parahaemolyticus in bioanalysis. Highlights: A novel turn-on fluorescence method for robust detection of V. parahaemolyticus. Proposed one-step detection system is sensitive and selective without pre-enrichment. A specific IgY was used for V. parahaemolyticus detection in various food samples.